DAMPAK BENSIN TANPA TIMBAL (Pb) PADA SEMESTER PERTAMA TERHADAP KUALITAS UDARA KOTA DENPASAR - GEDE SUGIARTA, ANAK AGUNG (Bumi Lestari, 2012)
This study was to effect premium the air quality composition at Denpasar City. The objective test were carried out at a 3 place overload to transportation at Denpasar city and critical quality parameters of Pb. The results indicated that the recommended air quality composition is 88,298 NO2 at Gajah Mada Street and 521,48 CO at Suci Street.
Keywords: Premium, Denpasar City, Pb, Air quality